Abnormal Moral Reasoning in Complete and Partial Callosotomy Patients - Miller, Michael B. (2010)
Recent neuroimaging studies suggest lateralized cerebral mechanisms in the right temporal parietal junction are involved in complex social and moral reasoning, such as ascribing beliefs to others. Based on this evidence, we tested 3 anterior-resected and 3 complete callosotomy patients along with 22 normal subjects on a reasoning task that required verbal moral judgments. All 6 patients based their judgments primarily on the outcome of the actions, disregarding the beliefs of the agents. The similarity in performance between complete and partial callosotomy patients suggests that normal judgments of morality require full interhemispheric integration of information critically supported by the right temporal parietal junction and right frontal processes.